Crystallographic and Geometric Factors in the Shear Development in <001> FCC Single Crystals: Molecular Dynamics Simulation and Experimental Study - Lychagin D. V. Dmitry Vasiljevich; Dmitriev A. I. Andrey Ivanovich; Nikonov A. Yu. Anton Yurjevich; Alferova (Alfyorova) E. A. Ekaterina Aleksandrovna (2020, 2020)
Title screen